Altmetrics as alternative tool for measuring the impact of scholarly documents based on readers attention: A Comparative Study - Jabur, Naeema H. (Qualitative and Quantitative Methods in Libraries, 2017)
There is no doubt that scholarly journal articles have received sufficient attention to measure their impact factor by counting the average number of citations to their contents.  Thus, citations have been considered as an academic tool to assess and evaluate the scholarly papers.  The conclusion of such measurement will be used to distinguish the highly cited journals, authors or article from those which are poorly cited and counted of no impact.  Since 2009, and with the explosion of the increasingly disseminated electronic content, scholars have increased their reading of article papers up to "50 percent more than they did in the 1970s, spending less time on average with each one"  (Renear and Palmer, 2009). Consequently, other alternative reading measurement along with the already existed traditional measure was required.  That is to deliver a richer impression of how to quantify a product is being reached, shared, used and saved. (Tananbaum, 2013:3-4)